Pengaruh Pendampingan Suami Terhadap Penurunan Kecemasan Fase Aktif Kala I Di Rsud Kardinah Kota Tegal - Uswatun Insani; Rima Armala (Jurnal Rumpun Ilmu Kesehatan, 2022)
Labor is the occurrence of the opening and thinning of the cervix and fetus into the birth canal which this process can cause anxiety. This study aims to apply husband assistance to reduce the anxiety felt by mothers with the length of the labor process at Kardinah Hospital, Tegal City. This research is a descriptive research with a case study approach. Research subjects are clients with primigravida or pregnancy for the first time who experience anxiety during the delivery process. The results of the case study research with husband assistance to reduce anxiety using the HARS Scale in patient 1 with a score of 34 after husband assistance experienced a decrease in anxiety to 20 and in patient 2 who previously experienced it with a score of 33 after husband mentoring experienced a decrease in anxiety to 21. Patients with Anxiety when facing the length of the labor process requires assistance from the husband which aims to reduce the anxiety felt by the mother during the delivery process.